The establishment of the Sea Turtle Conservation and Marine Pearl Educational Tourism Website in Sumbreng aims to promote ecosystem balance. - Devina Puspita Sari; Galih Anindita; Edy Setiawan; Aminatus Sa'diyah; Purwidi Asri; Ni'matut Tamimah; Ii Munadhif; Ponti Almas Karamina; Syafiuddin; Anggara Trisna Nugraha; Suci Indaryani; Mukhammad Jamaludin; Muhammad Bilhaq Ashlah; Muhammad Izzul Haj; Diego Ilham Yoga Agna; Salsabila Ika Yuniza; Faris Riyadi; Fajar Rahmat Adzani; Andika Aldo Pratama; Rahmania Firdiansyah; Laili Agustin Widyaningrum (Frontiers in Community Service and Empowerment, 2024)
The coast is an area that has potential for tourist attractions, including for turtle conservation which is relied on as a support for the economy. Turtles are one of the protected animals, not just protected by law because they are feared they will become extinct. The Turtle Conservation "Pearl of the Masaran Sea" which is located on Sumbreng Beach, East Java, is one of the turtle conservation areas developed by the Trenggalek Lentera Society. Activities carried out at the turtle conservation site "Pearl of the Masaran Sea" include relocating turtle eggs, caring for turtle eggs, combing eggs, and also releasing hatchlings. There are 5 types of turtles that are protected on Sumbreng beach, some of which are green turtles and hawksbill turtles which are included in the Appendix I category, which means they are prohibited from being traded internationally. Apart from visiting tourists being able to see the turtle breeding process, this conservation also provides economic tourism such as small Jeep facilities that are used to get around the beach and releasing hatchlings in certain months. However, due to lack of exposure to this conservation area. This resulted in a small number of tourists coming, and also some tourists coming in the wrong month and not being able to see the hatchlings being released onto the beach. Therefore, this service presents an innovation in the form of a website facility that is useful for updating all activities taking place at the "Pearl of the Masaran Sea" Turtle Conservation. So it can attract more tourists to visit this tourist attraction and tourists can also find out which months are effective for visiting this tourist attraction. It is hoped that the "Pearl of the Masaran Sea" turtle conservation will have the potential for educational tourism which can be developed further, so that it can support the economy of the surrounding community and can also be used as a source of income for managing the turtle conservation itself.